Statistical Analysis of Pensions and Incomes of Old Generation in Russia and Tomsk Region; Innovation Management, Development Sustainability, and Competitive Economic Growth - Ryzhkova M. V. Marina Vyacheslavovna; Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Kanov V. I. Viktor Ivanovich (2016, 2016)
Title screen